Fuzzy Logic untuk Menentukan Status Gizi Pada Rumah Sakit M. Zein Painan-Pessel - Fitri Anita, S.Kom.,M.Kom (JURNAL MANAJEMEN PENDIDIKAN, 2016)
Abstract Human life is crowded and busy often make a person forget the health and forget to pay attention to the nutrients in the food consumed . While in a healthy body can be judged from the meet nutrient needs. It can simply be described the sense of nutritional intake is all the body needs to be healthy , which is obtained from the nutritional intake of foods containing carbohydrates , protein , fat , vitamins and nutritional mineral.Pemenuhan balanced according to the condition of the body in order to meet health standards sometimes be an obstacle to set nutrition impartial. Therefore, this system created in order to help some parties such as nutritionists hospital, the governing party of nutrition of the patient, and so by applying fuzzy logic ( FL ) that helps provide provisions necessary criteria to identify the age , height , and weight body. By doing the calorie calculation method of fuzzy logic ( FL ) is expected to produce the right decisions about nutrition intake for the patient .Keywords : Fuzzy Logic To determine the Nutritional Status